Enhancing English Learners’ Comprehension Through Semantic Strategies in Classroom Discourse - Calvyn Sepanya Siregar; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This paper investigates how semantic strategies employed in instructional discourse influence English learners’ comprehension. Grounded in theories of speech acts, semantics, and sociolinguistics, the study explores how meaning is both conveyed and negotiated through classroom interaction. Through a qualitative, library-based analysis, it identifies core semantic patterns such as cohesive devices, modality, referential expressions, and clarification techniques that enhance the meaning-making process. The study also highlights how teachers' semantic awareness can scaffold learner engagement and support deeper comprehension. Findings underscore the importance of purposeful language planning, suggesting that explicit focus on semantic strategies can lead to more meaningful and effective English instruction. The study further identifies practical implications for English teachers, highlighting the benefits of fostering semantic awareness in classroom talk to improve learner autonomy and interpretive skills.